Wzniosłość jako koło zamachowe grozy. O wpływie estetyki Edmunda Burke’a i Immanuela Kanta na literaturę romantyzmu - Barski, Kamil (Załącznik Kulturoznawczy, 2022)
The article is an attempt to synthesize the basis information about the influence of Edmund Burke’s and Immanuel Kant’s esthetics on fear and its depictions in the literature of Gothic and Romanticism. This subject should be considered as important, because for the artist of those two trends the terror was one of the most popular methods of obtaining the effect of sublimity. The problem is analyzed in context of theory of literature and aesthetics. Therefore, the emphasized issue is not the interpretation of particular poems, but description of the phenomenon and gathering available sources. Adduced literary works are, as a consequence, an illustration of the thesis. The paper was thought as a handy compass, base for further interpretation wanderings. It opens with the depiction of this area of Burke’s esthetics, in which sublimity is united with terror. This last one is elicited by the pictures of danger, death etc., but – because of the distance, which is guaranteed by literature – when it is connected with motifs such as infinity or vastness, it can evoke sublimity. The next part of the article is an attempt at the description of Kant’s views and at connecting them with art – because, unfortunately, the philosopher did not trouble himself with the latter. The last fragment of the paper is an attempt to see the sublime through the Freudian psychoanalysis, which reveals other fears which hide behind well known motifs associated with sublimity and terror.